Dynamics of functional capabilities of the power supply systems of female skiers of high qualification specializing in various types of competitive activities - Golovachev, A. I.; Kolykhmatov, V. I.; Shirokova, S. V. (Vestnik sportivnoj nauki; Sports science bulletin, 2019)
The study identified specific manifestations of the formation of the functionality of the main energy systems (oxidative and lactacide) in skiers with different competitive orientation (distance, universality, sprint) at different stages of the preparatory period under the influence of strictly regulated construction of training loads aimed at improving the basic level of physical fitness, by increasing the total cyclic load in the range of 9300-9500 km. The results of the study show that the feature of the formation of the functional state of skiers at the beginning of the preparatory period in all training groups (Distance,station Wagons and Sprint) is the low implementation readiness due to the low level of activity of the lactacidic system, whichwas the highest in the group Distance, and combined with a higher level of functioning of the oxidative system and the state of intersystem regulation. A feature of the formation of the functional state of skiers-racers at the end of the preparatory period is the leveling of differences in the level of physical performance, and in the groups of Universals and Sprint in relation to the group Distance, mainly due to the increase in the power capabilities of the lactacid energy system.